Molecular identification and functional characterization of the first Nα-acetyltransferase in plastids by global acetylome profiling - Trinh, Dinh-Van; Linster, Eric; Feldman-Salit, Anna; Hell, Rüdiger; Wirtz, Markus (Proteomics, 2015)
Protein Nα-terminal acetylation represents one of the most abundant protein modifications of higher eukaryotes. In humans, six Nα-acetyltransferases (Nats) are responsible for the acetylation of approximately 80% of the cytosolic proteins. N-terminal protein acetylation has not been evidenced in organelles of metazoans, but in higher plants is a widespread modification not only in the cytosol but also in the chloroplast. In this study, we identify and characterize the first organellar-localized Nat in eukaryotes. A primary sequence-based search in Arabidopsis thaliana revealed seven putatively plastid-localized Nats of which AT2G39000 (AtNAA70) showed the highest conservation of the acetyl-CoA binding pocket. The chloroplastic localization of AtNAA70 was demonstrated by transient expression of AtNAA70:YFP in Arabidopsis mesophyll protoplasts. Homology modeling uncovered a significant conservation of tertiary structural elements between human HsNAA50 and AtNAA70. The in vivo acetylation activity of AtNAA70 was demonstrated on a number of distinct protein Nα-termini with a newly established global acetylome profiling test after expression of AtNAA70 in E. coli. AtNAA70 predominately acetylated proteins starting with M, A, S and T, providing an explanation for most protein N-termini acetylation events found in chloroplasts. Like HsNAA50, AtNAA70 displays Nε-acetyltransferase activity on three internal lysine residues. All MS data have been deposited in the ProteomeXchange with identifier PXD001947 (http://proteomecentral.proteomexchange.org/dataset/PXD001947).